An integrated three-flow approach for front-end service composition / Lim Mei Ting - Lim , Mei Ting (2020)
End-User Service Composition (EUSC) aims to enable end-user programmers who are not professional developers, develop applications by composing or aggregating existing web services. Despite the effort, studies have shown that end-user programmers are not able to deal with the technical complexities involved in EUSC. One way to deal with this issue is Front-End Service Composition (FESC), which allows end-user programmers to compose web services at the presentation layer of an application by configuring User Interface (UI) widgets that represent the back-end web services. However, apart from there not being enough studies on FESC, end-user programmers also experience a number of conceptual and usability issues in service composition. Following that, this research proposes an integrated three-flow approach namely application flow, control flow and data flow, to help deal with the current limitations of FESC. The approach generates the Graphical User Interface (GUI) of web services automatically, thus allowing the UI of the application to be developed at the same time the required web services are assembled. The approach allows end-user programmers to explicitly configure the three different types of flows involved in service composition. A proof-of-concept prototype, QuickWSC, that incorporates the three-flow approach was developed. It adopts a side-by-side multiple-view design to support visual configuration of the three flows in an uncluttered yet synchronized manner that adheres to established design guidelines. A user evaluation study which comprised the think-aloud protocol, observation and survey was conducted for data collection purpose where end-user programmers were recruited to evaluate QuickWSC. During the user evaluation study, the end-user programmer was given a brief introduction about the research. Thereafter, a predefined scenario was given to the end-user programmer for a web service composition task. The composition process was recorded on video for data analysis purposes. Framework analysis approach and descriptive statistics were used for qualitative and quantitative data analysis respectively. The results achieved was decently positive. Triangulation was performed during discussion over the results by using the qualitative and quantitative analysed data, and providing a more comprehensive finding of the prototype usability and its features. The evaluation results show that QuickWSC has a high level of usability and it is easy to compose web services by explicitly specifying the three flows, the three-flow configurations integrated into the two views helps in composing application from web services, and that no technical knowledge is required to use QuickWSC. This research has successfully implemented the prototype based on the proposed approach to address a number of conceptual and usability issues in service composition faced by the end-user.